An antimicrobial composition. - Abu Bakar, Fatimah; Hafidh, Rand Riadh; Abdulamir, Ahmed Sahib; Jahanshiri, Fatemeh (2011)
The present invention relates to an antimicrobial composition for use as antiviral, antibacterial and antifungal agent from natural product. The composition comprises an active ingredient with an effective amount of Vigna radiate L. extract.